“Little” Immortality: Immortological Theme in the Internet Microformats - Artur A. Dydrov; Milena S. Vizgina (Corpus Mundi)
This article correlates in content with the previous article in the journal. Internet microformats (short stories, gifs, pics, memes, demotivators, etc.) have a short life compared to “monumental” content, but are characterized by a high speed of circulation and reproduction. Metaphorically, this allows us to designate their life cycle and the specifics of penetration into the information environment, and from there to the consumer, as “virulent”. However, unlike the previous publication, this article has a different specialization. We have shifted our focus from considering trending memes in 2024 to the topic of corporeality and immortality. The correction of the focus is due to several reasons: firstly, immortality does not have a clearly established status (science / parascience / philosophical concept). At the same time, immortological ideas are integrated into the current agenda of intellectual communities and cultural spheres (business, intelligentsia, politics, religion, science), and claim to implement reformist projects (letters from “Russia 2045” to the president, the organization of the part «Evolution 2045», etc.). Secondly, immortality is associated with a deep desire, an archetypal mode of human existence, reproduced in mythology (search for a source in nature), religion (afterlife), art (religious and mythological plots), philosophy (cosmism), and science (?). The role of the latter is claimed by the often identified immortality and transhumanism, operating with the concept of “practical immortality”. In microformats, the topic is diffracted, falling into different contexts. The goal of this article is not to reduce it to some common semantic denominator, but to provide a working assembly of popular patterns of immortality in tags and memes.